An optimizing technique for using MATLAB HDL coder - Kayed, Somaya; Elsayed, Ghada (Bulletin of the National Research Centre, 2023)
Background MathWorks has provided an invaluable tool for designing and implementing FPGAs. MATLAB HDL coder serves a dual purpose, providing a quick proof of concept on the one hand and providing the g an easy-to-use platform for testing and verification on the other. It has main drawbacks over these advantages; it generates a code that is not optimized for both area and frequency. Results In this paper, we provide a technique for optimizing both area and frequency without losing the main advantages. The most affecting problem we found is loops. This paper classifies loop writing purposes into two types. The first one is preferable and introduces ease of writing a few lines instead of repeating the code. The second type is the problem that we intended to solve. Type II loop is appearing when the algorithm should perform these lines for several clock cycles. Writing it traditionally, force the synthesizer to implement all the repetitive clock cycles as repetitive hardware to be done in one clock cycle. This clock cycle is wide in time and is slow in frequency. This paper introduces an optimization technique for this problem. We compare before and after the implementation of our proposed technique. Conclusions We used Xilinx Spartan 6 XC6SLX4-2CPG196 FPGA. Our proposed technique improves the number of slice LUTs (Look Up Tables) requirement from 366 to 72%. The frequency improved from: 26.574 to 185.355 MHz. Based on that, we now recommend using MATLAB HDL coder in FPGA Design.